EFL Students' Pronunciation Improvement through Speech - Lakuana, Nurhaida; Octasary, Magvirah; Mukmin, Mukmin; Maheri , Selis (BABASAL English Education Journal, 2024)
The objectives of this research are to find out whether using speech can improve the students’ pronunciation at the eleventh grade of SMA N 10 Pulau Taliabu or not. The researchers used speech as a medium to improve the students’ pronunciation in this research. They employed pre-experimental research with one group for pre-test and post-test. The research population was the eleventh-grade students of SMA N 10 Pulau Taliabu. The sample of this research was all of the students at the eleventh-grade that consist of 30 students. Then, the data were analysed statistically. According to the findings of the research, the use of speech is effective to improve the EFL students’ pronunciation at the eleventh grade students of SMA N 10 Pulau Taliabu. This result is proved through the  t–counted (19.17) was higher than the t-table (1.70113) by applying 0.05 level significance and degree of freedom (df) 29.